2022
DOI: 10.34133/2022/9892628
|View full text |Cite
|
Sign up to set email alerts
|

Low Infrared Emissivity and Strong Stealth of Ti-Based MXenes

Abstract: Advanced scenario-adaptable infrared (IR) stealth materials are crucial for creating localized closed thermal environments. Low emissivity over the broadest possible band is expected, as is superior mechanical deformability. Herein, we report a series of Ti-based MXenes with naturally low emissivity as ideal IR shielding materials. Over a wavelength ranging from 2.5 to 25 μm, Ti3C2TX film delivers an average emissivity of 0.057 with the lowest point of 0.042. Such a low emissivity coupled with outstanding stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…As shown in Figure S3, peaks located at 1460 and 1164 cm –1 , which can be respectively ascribed to the C–N stretching vibration and C–N in-plane ring deformation in the pyrrole ring, respectively, distinctly emerge in the spectrum of the BC@PPy product compared with the pure BC fiber. This fact strongly confirms the complete wrapping of PPy around BC after the polymerization reaction. All of these results demonstrate that BC fibers serve as substrates for the alignment of PPy chains and can effectively prevent the random aggregation of pyrrole oligomers, achieving the conformal coating of PPy. This is due to the strong hydrogen bonds formed between the −NH groups of PPy and −OH terminals on the surface of BC, resulting in a stable core–shell structure of BC@PPy fibers. In these composite nanofibers, BC functions as inner structure supports, while PPy performs as the conductive and active coating material.…”
Section: Results and Discussionsupporting
confidence: 60%
“…As shown in Figure S3, peaks located at 1460 and 1164 cm –1 , which can be respectively ascribed to the C–N stretching vibration and C–N in-plane ring deformation in the pyrrole ring, respectively, distinctly emerge in the spectrum of the BC@PPy product compared with the pure BC fiber. This fact strongly confirms the complete wrapping of PPy around BC after the polymerization reaction. All of these results demonstrate that BC fibers serve as substrates for the alignment of PPy chains and can effectively prevent the random aggregation of pyrrole oligomers, achieving the conformal coating of PPy. This is due to the strong hydrogen bonds formed between the −NH groups of PPy and −OH terminals on the surface of BC, resulting in a stable core–shell structure of BC@PPy fibers. In these composite nanofibers, BC functions as inner structure supports, while PPy performs as the conductive and active coating material.…”
Section: Results and Discussionsupporting
confidence: 60%
“…EDS studies revealed that oxygen and nitrogen were scattered with uniformity on the surface suggesting a scatter free EM pathway. Li et al devised an adaptable infrared shielding MXene film with an average emissivity of 0.057 for a broad band ranging from 2.5 to 25 μm [84], the shielding behaviour was reflection governed, however recently V 2 CTx and V 4 C 3 Tx MXenes showing absorption driven EMI shielding (90% efficiency) have also been reported [85].…”
Section: Defect Engineering Of Mxenementioning
confidence: 99%
“…[ 1 ] One example of MXene, Ti 3 C 2 F x , satisfies the stoichiometric ratio of n + 1/ n , in which M, X, and T stand for transition metals, carbon or nitrogen, terminal groups at surfaces, respectively. The MXene has exhibited extraordinary electrical, [ 2–4 ] optical, [ 5 ] mechanical, [ 6–8 ] and electrochemical properties [ 9 ] since its first discovery, [ 10 ] which has become an emerging material for sensing, [ 11,12 ] communication, [ 13,14 ] energy, [ 15,16 ] environmental, [ 17 ] and healthcare applications. [ 18–20 ]…”
Section: Brief Of Mxenementioning
confidence: 99%
“…[1] One example of MXene, Ti 3 C 2 F x , satisfies the stoichiometric ratio of n + 1/n, in which M, X, and T stand for transition metals, carbon or nitrogen, terminal groups at surfaces, respectively. The MXene has exhibited extraordinary electrical, [2][3][4] optical, [5] mechanical, [6][7][8] and electrochemical properties [9] since its first discovery, [10] which has become an emerging material for sensing, [11,12] communication, [13,14] energy, [15,16] environmental, [17] and healthcare applications. [18][19][20] There are many reviews existing for electrochemical energy storage, including supercapacitors, lithium ion batteries, [21][22][23] sodium ion batteries, zinc ion batteries, [24][25][26] lithium-sulfur batteries, and energy conversions, [27][28][29] includingThe Internet of Things era has promoted enormous research on sensors, communications, data fusion, and actuators.…”
mentioning
confidence: 99%